ANALISIS KINERJA PT. BANK PEMBIAYAAN RAKYAT SYARIAH SAFIR BENGKULU - Marpeka, Lismeza; Susena, Karona Cahya (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2016)
The purpose of this research is one of the efforts help the business person in assessing the performance of the companies (banking), namely to know how the performance of PT. BPRS SAFIR BENGKULU in the priode 2012-2014 if seen with the Balanced scorecard approach. The study was descriptive in nature with the quantitative approach, where the purpose of this descriptive study was to make a picture, or painting in a systematic, actual and accurate regarding the facts, properties and relationships between phenomena investigated. The collection of data on research is, interviewing, documentation, questionnaire by means of collecting data skunder and the data collected is financial reports in 2012, 2013, 2014. From the results of the measurement of overall performance showed that the performance of PT BPRS SAFIR BENGKULU already good views from all four financial perspective, the customer perspective, the perspective of internal business processes, and learning and growth perspective of the balanced scorecard.Keywords: Performance, Balanced Scorecard, Islamic Banking